2009
DOI: 10.1007/s00421-009-1012-y
|View full text |Cite
|
Sign up to set email alerts
|

Does oxidative capacity affect energy cost? An in vivo MR investigation of skeletal muscle energetics

Abstract: Investigations of training effects on exercise energy cost have yielded conflicting results. The purpose of the present study was to compare quadriceps energy cost and oxidative capacity between endurance-trained and sedentary subjects during a heavy dynamic knee extension exercise. We quantified the rates of ATP turnover from oxidative and anaerobic pathways with (31)P-MRS, and we measured simultaneously pulmonary oxygen uptake in order to assess both total ATP production [i.e., energy cost (EC)] and O(2) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
16
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 97 publications
7
16
1
Order By: Relevance
“…Although no corresponding results are available in children for the purpose of comparison, the results we obtained in adults are consistent with previous studies with similar end-of-exercise acidosis (61) and similar exercise conditions (45). Given that similar acceleration of pH recovery kinetics has been reported in highly endurance-trained athletes compared with lesstrained subjects (25,43), this result provides additional support for an enhanced oxidative capacity before puberty.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although no corresponding results are available in children for the purpose of comparison, the results we obtained in adults are consistent with previous studies with similar end-of-exercise acidosis (61) and similar exercise conditions (45). Given that similar acceleration of pH recovery kinetics has been reported in highly endurance-trained athletes compared with lesstrained subjects (25,43), this result provides additional support for an enhanced oxidative capacity before puberty.…”
Section: Discussionsupporting
confidence: 92%
“…The relative contributions of oxidative and anaerobic processes are tightly linked to exercise modality, i.e., intensity and duration, and individual capacity, e.g., fiber-type composition and training status (43). While differences among protocols might explain the various results reported so far, these issues also underline the importance of exercise standardization to properly compare subjects with obvious different muscle capacities.…”
mentioning
confidence: 95%
“…In the present study, we found that both the initial EC of muscle contraction and EC calculated over the entire exercise period were not influenced by the training status, regardless of the method used. These findings strongly support previous results (4,5), and confirm that unaltered EC is not related to any bias in the calculation method. It also contradicts the hypothesis of an altered efficiency caused by an increased aerobic fitness (51).…”
Section: Methods Effects On Inferences Related To Training Effects Dursupporting
confidence: 94%
“…Based on a computer simulation (Fig. 7), we illustrated that the rapid decrease in [PCr] at the onset of exercise potentially leads to a large reduction in DG ATP , which is further exacerbated by the transient alkalosis commonly observed during knee extension exercise at this intensity (4). As a result, for a given power output, more ATP would be required as long as [PCr] does not reach a steady state.…”
Section: Energy Costmentioning
confidence: 97%
See 1 more Smart Citation